Extremely chaotolerant and kosmotolerant Aspergillus atacamensis – a metabolically versatile fungus suitable for recalcitrant biosolid treatment - Moreno-Perlin, Tonatiuh; Valdés-Muñoz, Gisell; Jiménez-Gómez, Irina; Gunde-Cimerman, Nina; Yarzábal Rodríguez, Luis Andrés; Sánchez-Carbente, María del Rayo; Vargas-Fernández, Alfaniris; Gutiérrez-Cepeda, Adrián; Batista-García, Ramón Alberto (Frontiers in Microbiology, 2023)
Obligate halophily is extremely rare in fungi. Nevertheless, Aspergillus atacamensis (strain EXF-6660), isolated from a salt water-exposed cave in the Coastal Range hills of the hyperarid Atacama Desert in Chile, is an obligate halophile, with a broad optimum range from 1.5 to 3.4 M of NaCl. When we tested its ability to grow at varied concentrations of both kosmotropic (NaCl, KCl, and sorbitol) and chaotropic (MgCl2, LiCl, CaCl2, and glycerol) solutes, stereoscopy and laser scanning microscopy revealed the formation of phialides and conidia. A. atacamensis EXF-6660 grew up to saturating levels of NaCl and at 2.0 M concentration of the chaotropic salt MgCl2. Our findings confirmed that A. atacamensis is an obligate halophile that can grow at substantially higher MgCl2 concentrations than 1.26 M, previously considered as the maximum limit supporting prokaryotic life. To assess the fungus’ metabolic versatility, we used the phenotype microarray technology Biolog FF MicroPlates. In the presence of 2.0 M NaCl concentration, strain EXF-6660 metabolism was highly versatile. A vast repertoire of organic molecules ( 95% of the substrates present in Biolog FF MicroPlates) was metabolized when supplied as sole carbon sources, including numerous polycyclic aromatic hydrocarbons, benzene derivatives, dyes, and several carbohydrates. Finally, the biotechnological potential of A. atacamensis for xenobiotic degradation and biosolid treatment was investigated. Interestingly, it could remove biphenyls, diphenyl ethers, different pharmaceuticals, phenols, and polyaromatic hydrocarbons. Our combined findings show that A. atacamensis EXF-6660 is a highly chaotolerant, kosmotolerant, and xerotolerant fungus, potentially useful for xenobiotic and biosolid treatments.